2019
DOI: 10.1007/s00332-019-09588-7
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Spatio-temporal Time Series Using Dimension Reduced Local States

Abstract: We present a method for both cross estimation and iterated time series prediction of spatio temporal dynamics based on reconstructed local states, PCA dimension reduction, and local modelling using nearest neighbour methods. The effectiveness of this approach is shown for (noisy) data from a (cubic) Barkley model, the Bueno-Orovio-Cherry-Fenton model, and the Kuramoto-Sivashinsky model.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…In the following, a state space reconstruction v(t) of a single time series s(t) is used to further predict its course. Besides a very recent idea [90] to train neural ordinary differential equations on a reconstructed trajectory, which then allows prediction, several attempts have been published [10][11][12][13][14][15][16] which more or less rely on the same basic idea. For the last vector of the reconstructed trajectory, denoted with a time-index l, v(t l ), a nearest neighbor search is performed.…”
Section: Short Time Prediction Of the Hénon Map Time Seriesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the following, a state space reconstruction v(t) of a single time series s(t) is used to further predict its course. Besides a very recent idea [90] to train neural ordinary differential equations on a reconstructed trajectory, which then allows prediction, several attempts have been published [10][11][12][13][14][15][16] which more or less rely on the same basic idea. For the last vector of the reconstructed trajectory, denoted with a time-index l, v(t l ), a nearest neighbor search is performed.…”
Section: Short Time Prediction Of the Hénon Map Time Seriesmentioning
confidence: 99%
“…The famous embedding theorems of Whitney [1], Mañé [2], and Takens [3] together with their enhancement by Sauer et al [4] allow a high dimensional state space reconstruction from (observed) uni-or multivariate time series. Computing dynamical invariants [5][6][7][8][9] from the observed system, making meaningful predictions even for chaotic or stochastic systems [10][11][12][13][14][15][16], detecting causal interactions [17][18][19] or nonlinear noise reduction algorithms [20,21] all rely explicitly or implicitly on (time delay) embedding [22] the data into a reconstructed state space. Other ideas rather than time delay embedding (TDE) are also possible [22][23][24][25][26][27], but due to its simple use and its proficient outcomes in a range of situations, TDE is by far the most common reconstruction technique.…”
Section: Introductionmentioning
confidence: 99%
“…In the following, a state space reconstruction v(t) of a single time series s(t) is used to further predict its course. Besides a very recent idea [20] to train neural ordinary differential equations on a reconstructed trajectory, which then allows prediction, several attempts have been published [23,15,85,79,50,74,45] which more or less rely on the same basic idea. For the last vector of the reconstructed trajectory, denoted with a time-index l, v(t l ), a nearest neighbor search is performed.…”
Section: Short Time Prediction Of the Hénon Map Time Seriesmentioning
confidence: 99%
“…The famous embedding theorems of Whitney [97], Mañé [64], and Takens [88] together with their enhancement by Sauer et al [81] allow a high dimensional state space reconstruction from (observed) uni-or multivariate time series. Computing dynamical invariants [35,36,41,49,51] from the observed system, making meaningful predictions even for chaotic or stochastic systems [23,15,85,79,50,74,45], detecting causal interactions [86,24,98] or non-linear noise reduction algorithms [52,68] all rely explicitly or implicitly on (time delay) embedding [72] the data into a reconstructed state space. Other ideas rather than time delay embedding (TDE) are also possible [72,8,32,73,65,63], but due to its simple use and its proficient outcomes in a range of situations, TDE is by far the most common reconstruction technique.…”
Section: Introductionmentioning
confidence: 99%
“…In these "big data" days, a signi cant number of researchers are focusing on developing novel methods for time series forecasting based on machine learning algorithms. [10][11][12][13][14] Delay embedding and recurrent neural networks have been used to predict the evolution of chaotic systems such as the Lorenz system and the Mackey-Glass system. 15 Locally linear neurofuzzy models 16 and support vector machine 17 have also been used to forecast chaotic signals.…”
Section: Introductionmentioning
confidence: 99%